Strategi Dompet Dhuafa Dalam Pemberdayaan Masyarakat Miskin di Provinsi Jawa Timur - Putri, Annisa; Pambudi, Bayu Prasetyo; Aldiansyah, Septianto; Ristrianti, Yusniar Rah Ayu (Journal of Geographical Sciences and Education, 2024)
Dompet Dhuafa is a philanthropic institution sourced from funds from zakat, infaq, alms, and waqf as well as other halal funds aimed at empowering the poor through humanitarian activities and social entrepreneurship. Dompet Dhuafa takes part in community empowerment through activities aimed at reducing poverty in East Java by the second goal of the Sustainable Development Goals (SDGs). The data collection used in this study is a literature study based on available references. Dompet Dhuafa has various programs that can be implemented in East Java, namely the Poor Community Empowerment Program by providing training to improve skills. This program is also in line with the RPJPD, RPJMD, and RTRW of East Java Province. However, the dependence of recipients on assistance makes the community not independent. In addition, there is a thought from the recipient that the business capital lent by Dompet Dhuafa is not obligatory to be returned so the recommendations that can be given are that the recipient is expected to be more enthusiastic and participative.